1999
DOI: 10.1002/(sici)1097-4598(199902)22:2<151::aid-mus2>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography and magnetic resonance imaging in the evaluation of radiculopathy

Abstract: Electromyography (EMG) and magnetic resonance imaging (MRI) are commonly used in the diagnosis of cervical and lumbosacral radiculopathy, but the agreement between the two studies is unknown. We retrospectively studied 47 patients with a clinical history compatible with either cervical or lumbosacral radiculopathy who were evaluated with both an EMG and a spine MRI within 2 months of each other. Among these patients, 55% had an EMG abnormality and 57% had an MRI abnormality that correlated with the clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
3
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 20 publications
9
70
3
3
Order By: Relevance
“…Total agreement between EDX and MRI studies was 59.6 % similar to previous studies (60 %) [19], although the agreement between them in relation to the clinical findings was 49 %. MRI and EDX presented similar agreement with clinical findings in the ''definite'' group while agreement of MRI with clinical findings was higher in other two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total agreement between EDX and MRI studies was 59.6 % similar to previous studies (60 %) [19], although the agreement between them in relation to the clinical findings was 49 %. MRI and EDX presented similar agreement with clinical findings in the ''definite'' group while agreement of MRI with clinical findings was higher in other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of patients with clinically suspected radiculopathy, the sensitivity of electromyography (EMG) was reported to range from 49 to 86 % [19][20][21][22][23] based upon history and physical examination which is similar to the figure of 54 % (95 % confidence interval: 0.44-0.64) in the present study. Data on agreement of EDX and MRI with clinical findings in radiculopathy are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…More advanced disease may demonstrate significantly decreased nerve conduction, with axonal loss and evidence of demyelination in a multi-radicular pattern [16][17][18][19] . treatment Before any treatment proposal, it is important to know the natural history of the disease.…”
Section: Radiological Findingsmentioning
confidence: 99%
“…In fact, one study found EMG to have a sensitivity of 72% and a specificity of 85% in neurologically abnormal patients (41). Further research has shown abnormal EMGs in 35% to 64% of patients with radicular leg pain, and in 51% to 86% of those with abnormal neurologic examinations (42). The most common pattern of EMG findings in LSS appears to be multiple, bilateral lumbosacral radiculopathies, occurring with the following frequencies: L5 (48%), S1 (30%), L4 (17%), L3 (5%), S2 (4%), and L2 (3%) (43).…”
Section: N Ne Ee Ed DL Le E E Em Mg Gmentioning
confidence: 99%